The Influence of Visual Media on Postpartum Contraception Knowledge in Postpartum Mothers at Soasio Community Health Center - Yanti Idris; Raden Maria Veronika Widiatrilupi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Adequate knowledge about postpartum contraception is essential for postpartum women to prevent unintended pregnancies and maintain reproductive health. However, many postpartum women still have limited knowledge, which can lead to inappropriate contraceptive choices. Visual media is considered an effective educational tool because it can present complex information in a clear and engaging way. Objective: This study aims to analyze the effect of visual media on improving postpartum contraception knowledge among mothers at the Soasio Community Health Center. Methods: A quasi-experimental design with a pre-test and post-test approach was used. The sample consisted of 30 postpartum mothers selected through purposive sampling. Data were collected using a validated questionnaire on contraceptive knowledge. The intervention involved health education using visual media such as videos, posters, and infographics. Data analysis was conducted using the Wilcoxon Signed Rank Test to assess differences before and after the intervention. Results: Before the intervention, most respondents had poor to moderate knowledge, with only a small proportion demonstrating good understanding. After receiving education through visual media, there was a clear improvement, with the majority of respondents achieving good knowledge levels. Statistical analysis showed a significant increase (p < 0.05). Conclusion: Visual media effectively improves postpartum contraception knowledge and can be applied in primary healthcare settings to enhance reproductive health literacy.